A new embryonic pattern in parasitic wasps: divergence in early development may not be associated with lifestyle. Issue 6 (November 2013) - Mancini, Donato; Garonna, Antonio P.; Pedata, Paolo A.
SUMMARY Comparative embryogenesis of Encarsia formosa and Encarsia pergandiella (Hymenoptera Aphelinidae), two endoparasitoids of whiteflies (Hemiptera Aleyrodidae), revealed two strongly diverging developmental patterns. Indeed, the centrolecithal anhydropic egg of E. formosa developed through a superficial cleavage, as it occurs in Nasonia vitripennis, Apis mellifera, and Drosophila melanogaster. In contrast, the alecithal hydropic egg of E. pergandiella developed through holoblastic cleavage within a specialized extra‐embryonic membrane (EEM). Since this developmental pattern evolved independently in several lineages of hymenopteran endoparasitoids, departures from the superficial cleavage mode have been argued to be strongly canalized in response to a shift from ecto‐ to endoparasitic lifestyle. Coexistence of both developmental patterns in two congeneric species suggests that alterations of early embryonic development may not be correlated with lifestyle. In addition, embryogenesis of E. pergandiella exhibited the following developmental novelties compared to other species possessing a hydropic egg: (i) polar body derivatives early acquired a cytoskeletal boundary prior to any other cellularization event; (ii) cellularization was asynchronous, starting with an early differentiation of a single apical blastomere at the end of the third cleavage; (iii) appearance of cytoskeletal boundaries of embryo blastomeres occurred between the third and fourth cleavages; (iv) the EEM originated through asynchronous participation of three separate lineages of cleavage nuclei, one of which associated with the polar body derivatives in a syncytium. Our results confirm a scenario of high plasticity in the early developmental strategies of hymenopteran endoparasitoids.